Antioxidant and Anti-Inflammatory Activities in Relation to the Flavonoids Composition of Pepper (Capsicum annuum L.) - Soo-Yeon Cho; Heon-Woong Kim; Min-Ki Lee; Hyeon-Jung Kim; Jung-Bong Kim; Jeong-Sook Choe; Young-Min Lee; Hwan-Hee Jang (MDPI AG, 2020)
The chili pepper (Capsicum annuum L.) is a food source that is rich in flavonoids such as luteolin and apigenin. Flavonoids are known to have anti-inflammatory and antioxidant activities; however, studies on the flavonoids composition identified and the anti-inflammatory and antioxidant effects in pepper leaves (PL) and fruits (PF) are insufficient. In the present study, we investigated the antioxidant and anti-inflammatory effects in vitro, and the flavonoids contents of the PL and PF. Pepper extracts showed radical scavenging activities and ameliorated the lipopolysaccharide (LPS)-stimulated inflammatory response by decreasing nitric oxide production and interluekin-6 and tumor necrosis factor alpha levels in RAW 264.7 cells, with more effective activities noted for PL than for PF. Furthermore, PL extracts markedly inhibited the LPS-induced production of reactive oxygen species accumulation. The flavonoid profile and content of pepper were dependent on the part, with PL showing higher total flavonoids than PF. In particular, the content of luteolin glycosides in PL was twice that in PF. Thus, PL may be useful to prevent oxidative stress and inflammation-related diseases.